Dhammadesana management at the Tantrayana Buddhist religious assembly zhenfozong kasogatan Indonesia Central Lampung branch administrator - Damana, I Ketut (Institute of Computer Science (IOCS), 2024)
This research aims to administer the dhammadesana method at the Lampung branch of the Tantrayana Buddhist religious assembly. This research uses a qualitative method with a descriptive approach. The data collection techniques used in the research were interviews and documentation. The validity used in this research uses source triangulation techniques which can differentiate the author's information from the theory used by informants in this research which consists of; region and city. Data analysis techniques are carried out through reduction, presentation and drawing conclusions. The results of research in managing dhammadesana give a feeling of joy. This has gone according to expectations, with a focus on four main aspects, namely planning, organizing, directing and monitoring. The research results show that it can provide contribution value to the sustainable development of dhammadesana management theory and practice in the Lampung assembly.